Mechanism design and kinematic analysis of a robotic manipulator driven by joints with two degrees of freedom (DOF). Issue 1 (15th January 2018) - Huang, He; Dong, Erbao; Xu, Min; Yang, Jie; Low, Kin Huat
Abstract : Purpose: This paper aims to introduce a new design concept for robotic manipulator driven by the special two degrees of freedom (DOF) joints. Joint as a basic but essential component of the robotic manipulator is analysed emphatically. Design/methodology/approach: The proposed robotic manipulator consists of several two-DOF joints and a rotary joint. Each of the two-DOF joints consists of a cylinder pairs driven by two DC motors and a universal joint (U-joint). Both kinematics of the robotic manipulator and the two-DOF joint are analysed. The influence to output ability of the joint in terms of the scale effect of the inclined plane is analysed in ADAMS simulation software. The contrast between the general and the proposed two-DOF joint is also studied. Finally, a physical prototype of the two-DOF joint is developed for experiments. Findings: The kinematic analysis indicates that the joint can achieve omnidirectional deflection motion at a range of ±50° and the robotic manipulator can reach a similar workspace in comparison to the general robotic manipulator. Based on the kinematic analysis, two special motion modes are proposed to endow the two-DOF joint with better motion capabilities. The contrast simulation results between the general and the proposed two-DOF joints suggest that the proposed joint can perform better in the output ability. The experimental results verify the kinematic analysis and motion ability of the proposed two-DOF joint. Originality/value: A new design concept of a robotic manipulator has been presented and verified. The complete kinematic analysis of a special two-DOF joint and a seven-DOF robotic manipulator have been resolved and verified. Compared with the general two-DOF joint, the proposed two-DOF joint can perform better in output ability.